Sistem Informasi Industri Kecil Menengah Berbasis Sentra Menggunakan Metode Rapid Application Development - Annas Setiawan Prabowo; Nur Wahyu Rahadi (P3M Politeknik Negeri Cilacap, 2020)
Domestic economic growth in Indonesia has increased by 5% per year in the four year period of the implementation of the RPJMN (2015-2018). The Department of Manpower and Industry of Cilacap district has had IKM data that have been recorded manually using books. The problem that occurs is the agency difficulty in finding data as well as difficulties in monitoring the development of turnover, production capacity, assets, as well as the number of workers that change very quickly. Based on these problems, it is necessary to create a center-based small and medium industry information system to manage small-based center industries. This research uses the Rapid Application Development (RAD) method. The results of this study are the existence of an information system that is able to manage data of small and medium industries based on centers, the ability to find data quickly, and the ability to monitor developments in terms of turnover, assets, production capacity and number of employees.